DAMPAK ATRAKSI, AMENITAS DAN AKSESIBILITAS PANTAI PASIR PUTIH KABUPATEN MANOKWARI TERHADAP KEPUASAAN WISATAWAN BERKUNJUNG - Winny Virginia Saway; Stella Alvianna; Estikowati; Alwin Lasarudin; Syarif Hidayatullah (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2021)
Indonesia has the potential of diverse natural tourism attractions, making Indonesia one of the countries with the leading tourism sector that is famous in the world. Manokwari Regency is one of the areas in Indonesia that has a variety of beautiful natural attractions, the leading tourist attractions in Manokwari is Pasir Putih Beach. The purpose of this research is to find out how the relationship between Attractions, Amenities, and Accessibility offered by tourist attractions has an impact on Tourist Satisfaction in Pasir Putih Beach, Manokwari Regency, West Papua. This research focuses on the study of tourism, especially related to Attractions, Amenities, Accessibility, and Tourist Satisfaction. This research is explanatory, the population in this study is all people or people who have visited Pasir Putih Beach in Manokwari. The sample using a minimum sample amount is 5-10 times the number of statement items contained in the study. The number of question items in this study amounted to 12, so the maximum sample size of this study was 5 x 12 = 60. The process of collecting sample data through open questionnaires. Data analysis techniques using Multiple Linear Regression Analysis and Hypothesis Testing. The results of this study showed Attractions, Amenities, and Accessibility have a positive and significant effect on Tourist Satisfaction both partially and simultaneously, where Amenities is the most influential variable to the Satisfaction of White Sand Beach Tourists.